Analisis Pengalaman Wisatawan Saat Mengunjungi Destinasi Wisata MICE Halal “Muslim Life Festival 2022” - Gantina Suciati; Titing Kartika; Adrian Agoes (LPPM and Travel Operation Department Universitas Asa Indonesia, 2023)
Tourism activities will be worth the reward when visitors continue to carry out the obligations of things that have been determined in certain religious rules. In the context of Muslims, they will have certain needs when traveling for tourism. The research objective is to analyze a national event organized by PT.Lima Event entitled